A checklist of fungi in Oman - Maharachchikumbura, Sajeewa S. N.; Al-Sadi, Abdullah M.; Al-Kharousi, Moza; Al-Saady, Nadiya; Hyde, Kevin D. (Phytotaxa, 2016)
Mycologists and plant pathologists have long been documenting fungi in checklists or adding them to databases that list hosts and associated fungi. Most references to the fungi of Oman are scattered in journals, reports and university theses. A review of the fungal status of Oman is long overdue as soil-borne and plant pathogens have been studied to some extent. Although Waller & Bridge (1978) listed the fungal diseases on economically important crops in Oman, the present study is the first attempt to put together all hitherto recorded fungi from this part of the world. This paper presents a systematic checklist of 318 fungal species, in 173 genera, currently known to occur in Oman. A working checklist of accepted taxa in Oman is vital in progress of the systematics, agriculture, quarantine and many other applied scientific fields in the country.